Efeitos do enalapril e do captopril sobre a função renal e células sanguíneas de camundongos C57BL/6 tratados com N-metilglucamina in vivo - Oliveira, Suize Silva (2016)
The aim of this study was to determine whether enalapril and captopril would reverse the kidney damage caused by antimoniate N-methylglucamine in C57BL/6 mice and compare the mice treated with meglumine antimoniate in combination with inhibitors of angiotensin-converting enzyme (ACE inhibitors) - captopril and enalapril, highlighting the importance of knowing their actions on the total leukocyte count in the peripheral blood and bone marrow cells. used inbred mice, the C57BL/6 mice, females, obtained from the Oswaldo Cruz Foundation (FIOCRUZ ), Salvador BA. The mice were divided into four groups as follows: Group 1 received saline by intramuscular (IM) injection; Group 2 received Nmethylglucamine antimonate (IM); Group 3 received N-methylglucamine antimonate and captopril; Group 4: treated with N-methylglucamine antimonate and enalapril. Both enalapril and captopril were administered orally in drinking water (ad libitum). After 30 days of treatment, animals were sacrificed and their kidneys were collected for histological analysis. The results revealed that enalapril completely reversed edema, hyperplasia of podocytes and nucleus of epithelial cells of proximal convoluted tubules caused by N-methylglucamine antimonate. Moreover, captopril treatment partially inhibited the harmful effects caused by Nmethylglucamine antimonate, kidney. Enalapril treatment increased the total number of bone marrow cells, when compared to the control. Taken together, we conclude that enalapril and captopril reverse edema and renal hyperplasia caused by N-methylglucamine antimonate in mice. The association of enalapril meglumine antimoniate shown to have a regulatory role in the number of bone marrow cells.